Are isothiocyanates and polyphenols from Brassicaceae vegetables emerging as preventive/therapeutic strategies for NAFLD? The landscape of recent preclinical findings - Bacil, Gabriel P. [UNESP]; Cogliati, Bruno; Cardoso, Daniel R.; Barbisan, Luís Fernando [UNESP]; Romualdo, Guilherme R. [UNESP] (Royal Society of Chemistry (RSC), 2022)
Nonalcoholic fatty liver disease (NAFLD) is a lipid impairment-related chronic metabolic disease that affects almost 25% of the worldwide population and has become the leading cause of liver transplantation in the United States of America (USA). NAFLD may progress from simple hepatic steatosis (HS) to nonalcoholic steatohepatitis (NASH), which occurs simultaneously in an inflammatory and fibrotic microenvironment and affects approximately 5% of the global population. Recently, NASH has been suggested to be a relevant driver in progressive liver cirrhosis and a population-attributable factor in hepatocellular carcinoma patients. Moreover, predictions show that NAFLD-related annual health costs in the USA have reached ∼$100 bi., but effective therapies are still scarce. Thus, new preventative strategies for this hepatic disease urgently need to be developed. The Brassicaceae vegetable family includes almost 350 genera and 3500 species and these are one of the main types of vegetables harvested and produced worldwide. These vegetables are well-known sources of glucobrassicin-derivative molecules, such as isothiocyanates and phenolic compounds, which have shown antioxidant and antilipogenic effects in preclinical NAFLD data. In this review, we gathered prominent evidence of the in vivo and in vitro effects of these vegetable-derived nutraceutical compounds on the gut-liver-adipose axis, which is a well-known regulator of NAFLD and may represent a new strategy for disease control.